Performance Assessment of Health Personnel with Passionate Performance Leaders as Moderators at the Badan Pengusahaan Batam Hospital - Isramilda; Wibisono, Chablullah; Satriawan, Bambang; Dewi, Nolla Puspita (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
One effort to maintain and improve hospital performance is by improving the performance of health workers. This situation makes hospitals create policies that employees must be able to become quality human resources, and it is not uncommon for employees to end up having double jobs, such as in the accreditation implementation process. This condition often becomes a source of conflict for employees, where employees become incompatible in carrying out their orders. The aim of this research is to build a model of employee performance at BP Batam Hospital, with the role of the leader to minimize the emergence of work stress due to workload which can reduce employee performance. This research was conducted at BP Batam Hospital, the research sample was 215 employees. Data processing uses the SEM method with PLS software. The results of this research conclude that pleasant employee experiences have a significant positive influence on employee performance, pleasant employee experiences have a significant positive influence on empowerment, empowerment has a positive and not significant influence on employee performance, work stress has a negative and not significant influence on pleasant employee experiences, engagement. Employees have a significant positive effect on enjoyable Employee Experience, work stress has a significant negative effect on employee engagement, work stress has a significant negative effect on the performance of health workers, work stress has a significant positive effect on performance through Enjoyable Employee Experience, work stress has a significant positive effect on Empowerment through Enjoyable Employee Experience, Employee Engagement have a significant positive influence on employee performance through Enjoyable Employee Experience, Employee Engagement has a significant positive influence on Empowerment through Enjoyable Employee Experience, Enjoyable Employee Experience has a positive and not significant influence on Employee Performance through Empowerment, Job Stress has a significant positive influence on Enjoyable Employees Experience through Employee Engagement, Enjoyable Employee Experience Has a Significant Negative Influence on Employee Performance Moderated by Leader Passionate Performance.